Optimal Operating Policies in the Presence of Exchange Rate Variability - Dasu, Sriram; Li, Lode (Management Science, 1997)
We study the structure of the optimal policies for a firm operating plants in different countries. The relative costs of production between the plants are assumed to vary over time due to economic and political factors such as exchange rates, inflation, taxes, and tariffs. Based on the costs, the firm can alter the quantity produced in each plant. We determine the structure of the optimal policies for deciding when and by how much to alter the production quantities. When the switch-over costs are linear or step functions, regardless of whether the variable production costs are concave or piece-wise linear convex, and regardless of whether the firm is supplying one or more markets, the optimal policy is always a barrier policy. The optimal barriers can be determined by using linear programming techniques, and the optimal costs can be computed by solving a system of linear equations. When the number of optimal barriers is two, the optimal expected costs and the condition that determines the optimal barriers are explicitly derived.